2014
DOI: 10.1259/bjr.20140212
|View full text |Cite
|
Sign up to set email alerts
|

Split-course accelerated hyperfractionated irradiation (CHA-CHA) as a sole treatment for advanced head and neck cancer patients—final results of a randomized clinical trial

Abstract: Objective: Evaluation of the efficacy and toxicity of splitcourse accelerated hyperfractionated irradiation (CHA-CHA) as a sole treatment for advanced head and neck (H&N) cancer patients. Methods: We enrolled 101 patients (39 in CHA-CHA and 37 in conventional (Conv.) arm completed the treatment). The CHA-CHA arm patients were irradiated twice a day, 7 days a week, using a fraction dose (fd) of 1.6 Gy up to 64 Gy with an 8-day gap in midterm. Patients in the control (Conv.) arm group were irradiated with a fd o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…There are several examples in other cancer types, associated with reduced toxicity while maintaining efficacy ( Pradier et al , 2004 ; Metcalfe et al , 2010 ; Fukuda et al , 2012 ; Gogna et al , 2012 ). The high metabolic response rates of the primary rectal cancer reported here support that this strategy warrants further study, but it should also be noted that split-course radiation was reported to have a negative impact in head and neck ( Daoud et al , 2007 ; Miszczyk et al , 2014 ), gynaecological ( Pedersen et al , 1994 ), and anal cancers ( John et al , 1996 ).…”
Section: Discussionsupporting
confidence: 59%
“…There are several examples in other cancer types, associated with reduced toxicity while maintaining efficacy ( Pradier et al , 2004 ; Metcalfe et al , 2010 ; Fukuda et al , 2012 ; Gogna et al , 2012 ). The high metabolic response rates of the primary rectal cancer reported here support that this strategy warrants further study, but it should also be noted that split-course radiation was reported to have a negative impact in head and neck ( Daoud et al , 2007 ; Miszczyk et al , 2014 ), gynaecological ( Pedersen et al , 1994 ), and anal cancers ( John et al , 1996 ).…”
Section: Discussionsupporting
confidence: 59%
“…After screening the title and abstract and reading full texts, 55 of the 67 articles were subsequently excluded from the meta-analysis: 44 studies were related to other comparisons, 5 studies lacked usable data, 2 studies did not report relevant outcome, and 4 studies were not RCT. Finally, a total of 12 articles were included [7, 912, 1521]. The PRISMA research flowchart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Split Course Radiation Therapy (SCRT) refers to a regime of RT that is broken into at least two phases, with each phase being separated by a rest interval, usually four weeks, to allow for the healing of acute toxicities such as mucositis and desquamation. This method has been used in the treatment of head, neck [8] and anal cancers [9] but abandoned due to decreased local control thought to be due to accelerated repopulation [10]. However, SCRT could be coming back into vogue in scenarios similar to ours [11].…”
Section: Resultsmentioning
confidence: 99%